2003
DOI: 10.1046/j.1365-2567.2003.01711.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced mucosal and systemic immune responses to Helicobacter pylori antigens through mucosal priming followed by systemic boosting immunizations

Abstract: SUMMARYIt is estimated that Helicobacter pylori infects the stomachs of over 50% of the world's population and if not treated may cause chronic gastritis, peptic ulcer disease, gastric adenocarcinoma and gastric B-cell lymphoma. The aim of this study was to enhance the mucosal and systemic immune responses against the H. pylori antigens cytotoxin-associated gene A (CagA) and neutrophil-activating protein (NAP), through combinations of mucosal and systemic immunizations in female BALB/c mice. We found that oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 52 publications
2
41
0
Order By: Relevance
“…In particular, primeboost vaccination protocols, combining mucosal and parenteral administration, seem to be more promising than mucosal or parenteral alone in eliciting both cellular and humoral response (18,37), as well as in providing protection against H. pylori challenge (18). Although these protection data have been obtained by prophylactic vaccination, they should be taken in account in attempts to design a more efficacious protocol of therapeutic vaccination since, in this case, the infection can act as an effective mucosal priming (35).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, primeboost vaccination protocols, combining mucosal and parenteral administration, seem to be more promising than mucosal or parenteral alone in eliciting both cellular and humoral response (18,37), as well as in providing protection against H. pylori challenge (18). Although these protection data have been obtained by prophylactic vaccination, they should be taken in account in attempts to design a more efficacious protocol of therapeutic vaccination since, in this case, the infection can act as an effective mucosal priming (35).…”
Section: Discussionmentioning
confidence: 99%
“…Antigen specific IL-4 and IFN-γ responses from lymphocytes were measured using ELISPOT as previously described [46]. Briefly, 2 × 10 6 lymphocytes were added to polyvinyldifluoride plates (Millipore) precoated with rat anti-mouse IL-4 (Endogen, Woburn, MA) or rat antimouse IFN-γ (BD/Pharmingen, San Diego, CA) and blocked with complete RPMI 10% FBS.…”
Section: Antigen Specific Cytokine Assaysmentioning
confidence: 99%
“…Immunogenicity studies have also shown that the combination of mucosal priming followed by systemic boosting results in high antigenspecific antibody responses (25,39,40). However, in most H. pylori vaccine/protection studies immunized animals were challenged within a month after immunization, whereas we challenged the animals 3 months after immunization (11,13,15,20,24,34,35,43).…”
Section: Discussionmentioning
confidence: 99%
“…Antigen-specific cytokine assays. Antigen-specific IL-4 responses in lymphocytes from immunized mice were measured using an ELISPOT assay as previously described (40). Briefly, 2 ϫ 10 6 lymphocytes were added to polyvinylidene difluoride plates (Millipore) precoated with rat anti-mouse IL-4 (Endogen, Woburn, MA) and blocked with complete RPMI-10% FBS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation